On the Interactions of Tempo Radicals with Gold Nanostructures - Caroli-Rezende, M; Aliaga-Vidal, C; Aliaga-Vidal, C; Pastenes, C (Royal Society of Chemistry, 2018)
The direct binding of four TEMPO radicals to citrate-coated gold nanoparticles and nanoclusters was investigated by means of EPR, fluorescence spectroscopy, kinetic measurements, TEM imaging and microcalorimetry. Although some degree of binding between TEMPO or 4-hydroxy-TEMPO and gold nanoparticles could not be excluded, it was negligible when compared with binding with 4-amino or 4-carboxy-TEMPO, showing that binding takes place exclusively, or almost exclusively, via the 4-amino or 4-carboxy substituent. © 2018 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.